Clinical and epidemiological profile of COVID-19 patients hospitalized in the North of Mato Grosso: A cross-sectional study (Research, Society and Development, 2023)
Objective: Studies have shown that obesity, age, presence of chronic disease, respiratory disease and cancer are risk factors for COVID-19, increasing the risk of hospitalization, complications, and the mortality rate. Thus, the objective of this study was to compare and evaluate the clinical and epidemiological profile of COVID-19 patients admitted to the nursery or Intensive Care Unit (ICU) of the Hospital Regional Jorge de Abreu (HRJA) in Sinop-MT. Methods: This was a cross-sectional study with data collected from medical records of patients diagnosed with COVID-19 and admitted between March 2020 and March 2021. Results: Data from 399 patients hospitalized in a nursery and 389 in ICU were evaluated. Days of symptoms, age and body weight were significantly higher in ICU patients compared to nursery. Furthermore, it was observed that patients admitted to the ICU had a higher prevalence of obesity, diabetes, cardiovascular diseases, and other non-transmitted chronic diseases (NTCD). There was no difference between the groups regarding the presence of previous respiratory diseases. 82.2% of ICU patients and 18.8% of nursery patients required assisted mechanical ventilation. Percentage of patients requiring tracheostomy and presenting complications was also higher in the ICU. The mortality rate was significantly higher in ICU patients (75.2%) compared to nursery patients (13.9%). Conclusion: It was observed that the clinical and epidemiological profile of COVID-19 patients admitted to the ICU was more severe compared to those admitted to the nursery which can be associated with age, obesity and NTCD in these patients.